A STUDY OF RESEARCH PAPER-BASED QUESTIONNAIRE DESIGN METHODS USING CO-OCCURRENCE NETWORKS - Fujiyama, Kojiro; Masuda, Koji; Oktavianty, Oke; Haruyama, Shigeyuki (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
The creation of questionnaire forms based on research papers has been done for various purposes. In previous studies, the surveyor intentionally created questions to be used in questionnaires based on secondary research and the knowledge of the researcher, and it is unclear what procedure was used to create the questions. Therefore, in this study, we examined and discussed methods of mechanically creating questions based on a review of research papers. As a result, we proposed a new method to create questions by mechanically combining words obtained from the article search, text mining of extracted articles, and co-occurrence word search.